1995
DOI: 10.2135/cropsci1995.0011183x003500010007x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Developmental Morphology of Perennial Grasses

Abstract: Perennial forage grasses can be viewed as modular organisms. The phytomer is usually considered the basic unit of the grass plant and consists of a leaf blade and sheath, the internode, the node, and the associated axiliary bud below the point of sheath attachment. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 30 publications
3
116
0
6
Order By: Relevance
“…1). These results are similar to the trends described by Moore and Moser (1995), who reported that intermediate wheatgrass tiller density decreased as MSC increased. However, they determined that the vegetative phase ceased by DOY 156, but they ended their harvest on DOY 190.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1). These results are similar to the trends described by Moore and Moser (1995), who reported that intermediate wheatgrass tiller density decreased as MSC increased. However, they determined that the vegetative phase ceased by DOY 156, but they ended their harvest on DOY 190.…”
Section: Resultssupporting
confidence: 91%
“…The developmental morphology of these perennial grasses affects forage yield and quality and, hence, management decisions (Moore et al, 1991). Perennial grass tiller populations can be quantified to compare growth and developmental morphology (Moore and Moser, 1995).…”
mentioning
confidence: 99%
“…O intervalo de aparecimento de novas folhas está relacionado com a temperatura acumulada (MOORE & MOSER, 1995). Os dados de filocrono na primavera variaram de 173,4 a 209 GD, sendo próximos aos valores de 178,6 a 222,2 GD, encontrados por TRINDADE (1999) no perí-odo de primavera.…”
Section: Resultsunclassified
“…A unidade de tempo mais usada para o filocrono é a soma térmica, com unidade °C dia, a qual tem maior significado biológico em plantas do que dias do calendário civil, pois leva em conta o efeito da temperatura sobre o desenvolvimento vegetal (GILMORE & ROGERS, 1958;RUSSELE et al, 1984;McMASTER & SMIKA, 1988 (KIRBY, 1995;XUE et al, 2004), gramíneas forrageiras (FRANK & BAUER, 1995;MOORE & MOSER, 1995;ALMEIDA et al, 1997), alface (HERMES et al, 2001;DUARTE et al, 2005), arroz (NEMOTO et al, 1995;WALTER et al, 2005), batata (DELLAI et al, 2005), lírio (STRECK et al, 2004 ;SCHUH et al, 2005), meloeiro (STRECK et al, 2005a) e cártamo (STRECK et al, 2005b). Com relação ao tomateiro, estudos sobre emissão de folhas são escassos.…”
Section: Emissão E Expansão Foliar Em Três Genótipos De Tomateiro (Lyunclassified